Solitary Fibrous Tumor/Hemangiopericytoma Metastasizes Extracranially, Associated with Altered Expression of WNT5A and MMP9 - Hong, Jong-Hwan (Cancers (Basel), 2021)
SIMPLE SUMMARY: Meningeal/intracranial solitary fibrous tumor/hemangiopericytoma (icSFT/HPC) have a poor clinical outcome with metastatic behavior compared to soft tissue/extracranial SFT/HPCs (exSFT/HPC), but the underlying genetic factors are unclear. This study showed that WNT signaling, including WNT5A, was elevated in exSFT/HPC and MMP9 expression was higher in icSFT/HPC at both the mRNA and protein levels. Expression of CLDN5, a marker of endothelial tight junctions, was decreased in icSFT/HPC. The metastatic behavior of icSFT/HPC may be due to dysregulated angiogenesis and increased permeability of the vasculature caused by an altered WNT signaling pathway. Along with the increased expression of MMP9 in individual tumor cells, the combination of these effects will increase the probability of distant metastasis. Although exSFT/HPC and icSFT/HPC share a key molecular event, i.e., NAB2-STAT6 fusion, SFT/HPC may exhibit different biological properties and clinical courses depending on tumor location. ABSTRACT: Solitary fibrous tumor/hemangiopericytoma (SFT/HPC) is a mesenchymal tumor originating from various soft tissues and meninges, which carries the NAB2-STAT6 fusion gene. Meningeal/intracranial SFT/HPCs (icSFT/HPC) have a poor clinical outcome with metastatic behavior compared to soft tissue/extracranial SFT/HPCs (exSFT/HPC), but the underlying genetic factors are unclear. Differentially expressed genes (DEGs) were analyzed by NanoString nCounter assay using RNA extracted from formalin-fixed paraffin-embedded (FFPE) tissue samples. Additionally, immunohistochemistry (IHC) was performed on 32 cases of exSFT/HPC, 18 cases of icSFT/HPC, and additional recurrent or metastatic cases to verify the findings. Pathway analysis revealed that the WNT signaling pathway was enriched in exSFT/HPC. Analysis of DEGs showed that expression of WNT5A was lower and that of MMP9 was higher in icSFT/HPC than in exSFT/HPC (p = 0.008 and p = 0.035, respectively). IHC showed that WNT5A and CD34 expression was high in exSFT/HPC (p < 0.001, both), while that of MMP9 was high in icSFT/HPC (p = 0.001). Expression of CLDN5 in tumoral vessels was locally decreased in icSFT/HPC (p < 0.001). The results suggested that decreased WNT5A expression, together with increased MMP9 expression, in icSFT/HPC, may affect vascular tightness and prompt tumor cells to metastasize extracranially.